Presecretory and cytoplasmic invertase polypeptides encoded by distinct mRNAs derived from the same structural gene differ by a signal sequence. - Perlman, D (Proc Natl Acad Sci U S A, 1982)
Saccharomyces cerevisiae strain FH4C carries a single invertase structural gene, SUC2, but produces distinct invertase mRNAs and polypeptides for the secreted and cytoplasmic forms of the enzyme. The two major invertase cell-free translation products are polypeptides of 60,000 daltons (p60) and 62,000 daltons (p62) and correspond to the nonglycosylated cytoplasmic form of invertase and the precursor of glycosylated secreted invertase, respectively. This paper describes amino acid sequence and peptide map analyses of invertase polypeptides. The peptide maps demonstrate that p62, p60, and the in vivo secreted polypeptide have significant structural homology. Sequence analysis, however, revealed differences between p62 and p60 at their amino termini. p62 contains an amino-terminal signal sequence of 19 amino acid residues that is specifically cleaved during secretion in a cell-free system to generate the secreted 87,000-dalton invertase glycopeptide gp87. This signal sequence is not present in p60. p60 synthesis begins with a methionine which can be aligned with a methionine at residue 21 in p 62. During translation, the p60 initiator methionine is removed and the newly generated amino terminus is acetylated. Based on peptide map similarities, partial amino-terminal sequence data, and common genetic origin, it is suggested that p60 and p62 have identical amino acid sequences carboxy-terminal to the p60 initiator methionine (residue 21 of p62). The reciprocal correlations of signal sequence with secretion and absence of signal sequence with cytoplasmic localization provide proof of the signal hypothesis for secreted proteins. Two mechanisms are proposed for the derivation of p60 and p62 from a single structural gene: alternative promoter sites, and differential processing of a single primary transcript.